The EU-Turkey "Refugee deal": A new way of responsibility-sharing or the collapse of the international system for the protection of refugees? - Elitez, Ceren (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
AB-Türkiye "Mülteci anlaşması":Yeni bir sorumluluk paylaşımı yöntemi mi yoksa uluslararsı mülteci koruma sisteminin çöküşü mü?